Reconocimiento social de enfermería: opinión de la profesión en la actualidad - Ariana Janeth, Mazón Morejón (2020)
Social recognition is the way to reward a person for the proper exercise of their activities, for the nursing career is to increase their skills, abilities, and talents from the performance of their functions in any work environment. This work aims to determine the social recognition of nursing from the opinion of the profession today. A documentary, descriptive, comparative, and analytical study is presented, carried out between June-September 2020. A systematic review of documents published in electronic databases related to the subject was carried out, such as PubMed, Scielo, Dialnet, Cochrane Plus, Redalyc, Elsevier, University repositories, as well as national and international organizations (WHO /PAHO). The population consisted of 107 articles, leaving 46 bibliographies as a sample. The research consulted that the nursing profession is essential for maintaining the well-being of society, although it has been affected by stigmas that minimize or distort its functionality. Therefore, reward their work dependent on the generation of opportunities such as better working conditions, expansion of study systems, salary increases, managerial positions, and greater prestige. It was also evidenced that the professional must fight to vindicate the wrong perception that society has about nursing to recognize which is deserving. Most of the authors mention that the media are part of those who convey an inappropriate (sexist) and erroneous identity of a profession that is becoming increasingly complex and scientific.